ONLINE SHOP SEBAGAI ALTERNATIF BERBELANJA MASYARAKAT KOTA MANADO - Olii, Mohamad Rivai; Pratiknjo, Maria Heny; Rumampuk, Selvie (Universitas Sam Ratulangi, 2020)
The development of an online shop or online store through internet media is well known in Indonesia, and even well known by the general public, including the people of Manado. The many conveniences in shopping and the various types of products and services offered have made Manado people make online shops as an alternative shopping. This has made many Online Shop sellers offer their products in various ways to attract consumers to buy, they take advantage of the current pandemic where many people choose to shop from home.Many people in the city of Manado prefer online shops as an alternative to shopping rather than shopping at stores, malls, or other shopping places. Apart from being due to covid-19, there are several other reasons such as being practical and not complicated, no need to dress up, no need to leave the house, and no need to face heat and traffic jams.The purpose of this research is to find out how online shop as an alternative shopping for the people of Manado City. This study took data and an explanation of the Online Shop as an alternative to shopping for the people of Manado city in general. Informants were taken from various groups. The information that has been collected shows that many people in the city of Manado choose online shops as an alternative to shoppingKeywords: Online Shop, Online Shopping, Utilization of social media